Optimation of Auxin and Cytokinin on Enhanced Quality and Weight of Coffea liberica Somatic Embryos - Fitria Ardiyani; Edy Setiti Wida Utami; Hery Purnobasuki (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Coffea liberica is a variety of coffee that tolerant to marginal land, especially peatlands. One of propagation methods in C. liberica is somatic embryogenesis(SE) which producing large number of true-to-type plant seedlings in a short time. This research aimed at studying the effect of application of plant growthregulator (PGR) on quality and weight of somatic embryo of C. liberica. Somatic embryo in development stage was induced by Murashige and Skoog medium containing cytokinin as benzyl amino purin (BAP) and auxin as 2,4-dichlorophe-noxyacetic acid (2,4-D). While cotyledonary embryo in germination stage was induced by Murashige and Skoog medium containing cytokinin (BAP) and auxins as 2,4-D, indole acetic acid (IAA) and naphthaleneacetic acid (NAA). The resultsshowed that the application of auxins and cytokinins on development stage affected the formation of embryos, texture of calli, color of calli and embryos, and weight of somatic embryo. It also influenced the shoot and root formation, color and weight of geminating embryos of C. liberica at the germinating stage. During the development stage, addition of 1 mg/L BAP in the absence of 2,4-D in MS medium produced the highest quality of somatic embryo of C. liberica. This medium also produced heaviest somatic embryos but with lighter callus. While in germination stage, all medium treatments produced a typical germinating embryo. Coffea liberica germinating embryo growth optimally on MS medium containing 0.5 mg/L BAP as a single chemical or 0.5 mg/L BAP in combination with 0.5 mg/L IAA for shooting development. Whereas on rooting development, addition of 0.5 mg/L NAA on MS medium produced an optimal germinating embryo. Moreover, germination embryo of C. liberica recorded the highest in terms of dry weight on MS media with addition of 0.5 mg/L BAP. Application of appropriate concentration of auxin and cytokinin is needed to support the formation of somatic embryo and germinating embryo.